Dynamic memory to alleviate catastrophic forgetting in continual learning with medical imaging - Matthias Perkonigg (Nature Portfolio, 2021)
In clinical practice, the continuous progress of image acquisition technology or diagnostic procedures and evolving imaging protocols hamper the utility of machine learning, as prediction accuracy on new data deteriorates. Here, the authors propose a continual learning approach to deal with such domain shifts occurring at unknown time points.